„Animal” Symbolism in the Work of Günter Grass - Głuszko-Boczoń, Estera (The Motifs of Fauna and Flora in Literature and Culture, 2018)
The article aims to present diversity of animal symbolism in the work of the German Noble laureate. The animal motif — from dog to snail — is frequently explored by Grass. In numerous works, the animal plays a prominent role which allows to read the content in a multidimensional way. The animals foreshadow the future, forewarn and encourage reflection. They become a motif that gives room to further contemplation.